A LONG AND WINDING ROAD OF THE TOBACCO-FREE AREAS IMPLEMENTATION IN SEMARANG - Novia Handayani; Bagoes Widjanarko; Kusyogo Cahyo; Abdillah Ahsan; Dian Kusuma (Universitas Airlangga, 2023)
Background: The Tobacco-Free Areas (TFA) policy is an effective way to control the negative effects of smoking on the community, especially passive smokers. Semarang has had a TFA policy since 2013. However, some people still smoke freely in some areas, such as workplaces, kindergartens, and other public places. Aims: Identifying the implementation of Semarang City Local Government Regulation Number 3 of 2013 concerning Tobacco-Free Areas. Methods: This was qualitative research using the case study method. Data were collected using in-depth interviews with some key informants according to the inclusion criteria. Triangulation was conducted through observation and in-depth interviews with some informants. Data were analyzed using content analysis. Results: Some violations still occurred, mostly at the workplace and educational places, including government offices and schools. Violations happened due to inadequate support of the office's heads, insufficient workers and the society's awareness, policy rejection, inadequate financial support, lack of media exposure, and obscurity of the regulation articles, which led to misinterpretation. For example, Article 7, verse 3 states that the TFA regulation will be regulated by the mayor's decree. This statement weakens the regulation itself since the mayor's decree is not as strong as the local regulation. Conclusion: The implementation of Semarang City Local Government Regulation Number 3 of 2013 concerning Tobacco-Free Areas has not been carried out properly in all of the TFA areas. Violations were still found in many areas. Keywords: regulation, secondhand smokers, smoking, tobacco-free areas